Correlation between pupilometer and the vestibular/ocular motor screening in Division I female collegiate soccer athletes - Heick, J.; Entsler, L. (Neurology, 2020)
Objective The objective of this study was to explore the correlation between pupilometer and Vestibular Ocular Motor Screening on Division 1 female collegiate soccer players.